Operational Factors that Can Help Manufacturing Firms Transition to Green Enterprises - K. Agarwal, Ramesh (Technology Transfer and Entrepreneurship (Discontinued), 2015)
This paper examines some of the hindrances in moving the small and medium size manufacturing firms, with revenues ranging from U.S 1 to 50 million dollars, towards sustainability conscious and environmentally responsible corporate culture. Economic cost and benefits of transition to greener enterprise with greater energy efficiency and waste management in operations are estimated. Case studies of five manufacturing firms in the state of Missouri in US are conducted. Short and long term approaches to achieve the goals of energy conservation and waste/pollution reduction are determined in consultation with the company’s senior management; these are based on the evolutionary changes/innovations and economic sustainability. The companies are revisited after one year and two years to assess the implementation and its outcome. The successes and failures are noted and are used to generate new ideas and approaches. Some of the lessons learned can be used to improve the entrepreneurial approaches as the manufacturing firm transitions towards environmentally responsible economically sustainable enterprise.
Keywords: Transition to green enterprise